Health-promoting effects and everyday experiences with a mental health app using ecological momentary assessments and AI-based ecological momentary interventions among young people: qualitative interview and focus group study - Hiller, Selina; Götzl, Christian; Rauschenberg, Christian; Fechtelpeter, Janik; Koppe, Georgia; Wierzba, Eva; Sauter, Julia; Dietrich, Sina; Durstewitz, Daniel; Reininghaus, Ulrich; Krumm, Silvia (JMIR mhealth and uhealth, 2025)
Background: Considering the high prevalence of mental health conditions among young people and the technological advancements of artificial intelligence (AI)-based approaches in health services, mobile health (mHealth) apps for mental health are a promising way for low-threshold and large-scale mental health promotion, prevention, and intervention strategies, especially for young people. However, insufficient evidence on health-promoting effects and deficient user-centric designs emphasize the necessity for participatory methods in the interventions’ development processes. - Objective: This study aimed to explore young people’s everyday experiences using an AI-based mHealth app for mental health promotion based on ecological momentary assessments and ecological momentary interventions. Our analysis of qualitative data focused on exploring young people’s use patterns in daily life and mental health-promoting effects. - Methods: We conducted problem-centered interviews and focus groups with a subsample of 27 young people aged 14 to 25 years, who were among the participants of 2 microrandomized trials testing and evaluating an AI-based mHealth app (AI4U training). Our study used a participatory approach, with “co- and peer researchers” from the dialogue population actively engaged in research processes and data analysis. Structural content analysis guided the qualitative analysis. - Results: Participants reported enhanced emotional self-awareness and regulation in daily life through the ecological momentary assessments and ecological momentary interventions. Young people appreciated the AI4U training for managing emotions and stress. They had no trust issues regarding disclosing their mental health via the AI4U training in daily life. Some faced challenges integrating it into their daily routines and highlighted the value of autonomy in use decision-making processes. - Conclusions: Our findings reveal that young people benefited from enhanced emotional awareness and management through the use of the AI4U training, appreciating its anonymity for facilitating emotional disclosure. The results suggest that enhanced self-directed use may improve daily life integration, although participants noted that they sometimes avoided using the AI4U training during distress despite recognizing its potential benefits. These findings indicate the importance of balancing directed use and autonomy in digital interventions to harmonize compliance with effectiveness in daily life. We highlight the importance of participatory research for tailored digital mental health solutions.
Gesehen am 20.05.2025